2016
DOI: 10.12913/22998624/62629
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Pid Controller to Control a Fuel Cell Voltage Using the Imperialist Competitive Algorithm

Abstract: In this article, an optimized PID controller for a fuel cell is introduced. It should be noted that we did not compute the PID controller's coefficients based on trialand-error method; instead, imperialist competitive algorithms have been considered. At first, the problem will be formulated as an optimization problem and solved by the mentioned algorithm, and optimized results will be obtained for PID coefficients. Then one of the important kinds of fuel cells, called proton exchange membrane fuel cell, is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Sometimes multiple objectives are considered simultaneously in the optimization procedure. Such optimization problems involving several objectives are called the multi‐objective problems . The single‐objective optimization problems are solved with higher precision and much easier than the multi‐objective problems.…”
Section: Martials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes multiple objectives are considered simultaneously in the optimization procedure. Such optimization problems involving several objectives are called the multi‐objective problems . The single‐objective optimization problems are solved with higher precision and much easier than the multi‐objective problems.…”
Section: Martials and Methodsmentioning
confidence: 99%
“…Such optimization problems involving several objectives are called the multi-objective problems. 31,32 The single-objective optimization problems are solved with higher precision and much easier than the multi-objective problems. Thus, if possible, the single-objective approach could be employed in the optimization problems.…”
Section: Optimization Parabolic Trough Cpvt Systemmentioning
confidence: 99%
“…Although there are only speculative links between cyber-attacks and mass casualties, the high risk associated with infrastructure damage and loss of life and limb may be explained by their potentially catastrophic effects, the advantages they offer (making them a likely target as well as a significant source of concern if threatened), the inability to always identify perpetrators or their motivations, and expert disagreements that only exaggerate. 13 Although the impact of media coverage has yet to be thoroughly investigated, it may shed light on the substantial hazards that many people identify with cyber terrorism. Slovic also reminds us that kinetic terrorist attacks have high "signal value," or the idea that an incident will have a lasting impact and result in further devastation, death, and chaos.…”
Section: The Psychosomatic Impact Of Cyber Terrorismmentioning
confidence: 99%
“…In 2016, Shamel and et al [11] conducted a research called designing a PID controller to control a fuel cell voltage using the imperialist competitive algorithm. In 2017, Siddiqui et al [12] conducted a research called analysis and performance assessment of a new solar-based multigeneration system integrated with ammonia fuel cell and solid oxide fuel cell-gas turbine combined cycle, which showed that Increase of 19.3% in energy efficiency as compared to single generation system.…”
Section: Literaturementioning
confidence: 99%